2022
DOI: 10.3233/jhs-220679
|View full text |Cite
|
Sign up to set email alerts
|

Exploring college students’ fitness and health management based on Internet of Things technology

Abstract: The purpose of this paper is to help college students improve their physical health and build a sound health management system. The physical exercise and health management of college students following IoT (Internet of Things) are studied. First, the current situation of college students’ physical quality is analyzed, and it is found that the college students’ physical quality and mental states decline in recent years. Second, the connotation of health management is briefly introduced and its necessity is anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…An empirical study has also found that cognitive reappraisal adjustment strategy can improve HVC students' PR, while the use of expression inhibition strategy will hinder the promotion of PR [13] . In addition, cognitive reappraisal plays an intermediary role between emotional beliefs and depression [14] . People with high PR experience are found to have more positive and negative emotions than those with low PR [15] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…An empirical study has also found that cognitive reappraisal adjustment strategy can improve HVC students' PR, while the use of expression inhibition strategy will hinder the promotion of PR [13] . In addition, cognitive reappraisal plays an intermediary role between emotional beliefs and depression [14] . People with high PR experience are found to have more positive and negative emotions than those with low PR [15] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…After the government leadership in educational institutions has the authority to implement the rules and regulations for students. Therefore, effective implementation of rules for PE Education can be greatly influenced by the school leadership [12]. Moreover, the dedication to promoting physical education and fostering a supportive atmosphere for rules and routines have a direct relation with educational leaders.…”
Section: Factors Impacting the Implementation Of Rules And Routines I...mentioning
confidence: 99%
“…To assist university students, improve their physical health, He et al proposed a college student physical exercise and health management system based on the IoT era. The IoT-based physical exercise framework could strengthen the students' physical status [9]. Jiang proposed an engineering cost accounting system that combines chaotic data processing methods with IoT technology.…”
Section: Related Workmentioning
confidence: 99%